1996
DOI: 10.1172/jci118529
|View full text |Cite
|
Sign up to set email alerts
|

A somatically mutated human antiganglioside IgM antibody that induces experimental neuropathy in mice is encoded by the variable region heavy chain gene, V1-18.

Abstract: IgM paraproteins associated with autoimmune peripheral neuropathy and anti-Pr cold agglutinins react with sialic acid epitopes present on disialylated gangliosides including GD1b, GT1b, GQ1b, and GD3. A causal relationship between the paraprotein and the neuropathy has never been proven experimentally. From peripheral blood B cells of an affected patient, we have cloned a human hybridoma secreting an antidisialosyl IgM mAb, termed Ha1, that shows identical structural and functional characteristics to its serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 57 publications
(65 reference statements)
3
57
0
Order By: Relevance
“…IgG and IgM mAb's were then purified on HiTrap protein G (Supelco, Bellefonte, Pennsylvania, USA) and recombinant Protein L columns (Actigen, Cambridge, United Kingdom), respectively. mAb's were analyzed for monoclonality, light chain type, and subclass by isoelectric focusing and Western blotting using standard methods and reagents as described previously (16). The concentrations of all mAb's were measured using a radial immunoglobulin diffusion kit (Binding Site, Birmingham, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IgG and IgM mAb's were then purified on HiTrap protein G (Supelco, Bellefonte, Pennsylvania, USA) and recombinant Protein L columns (Actigen, Cambridge, United Kingdom), respectively. mAb's were analyzed for monoclonality, light chain type, and subclass by isoelectric focusing and Western blotting using standard methods and reagents as described previously (16). The concentrations of all mAb's were measured using a radial immunoglobulin diffusion kit (Binding Site, Birmingham, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…The basic structure of GQ1b and related gangliosides is shown in Figure 1. Mouse sera were tested for IgG and IgM response to gangliosides and LPSs by ELISA (16). Immunolon 2 microtiter plates (Dynatech, Ashford, United Kingdom) were coated with 200 ng ganglioside in methanol or 1 µg LPS in PBS per well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-GD3 mAb, R24, was a kind gift from Dr. Paul Chapman (Memorial Sloan-Kettering Cancer Center, New York, NY) and was used as a purified IgG. The human Ha1 and Pi1 IgM mAb were described and purified as reported previously [28,29]. Biotinylation of these antibodies was performed using the EZ-link biotinylation kit (Pierce, Cramlington, UK).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…To investigate the potential expression of ␣2,8-linked disialic acid moieties on the surface of NK cells, we used human IgM mAb Ha1 and Pi1, both of which are derived from patients with peripheral neuropathy [28,29]. In previous studies, these antibodies have been shown to react similarly with b-series gangliosides GD1b, GT1b, GQ1b, and GD3 in a manner consistent with their minimal epitope being NeuAc␣2,8- [30,31].…”
Section: Characterization Of Human Ha1 Antibody Which Recognizes Dismentioning
confidence: 99%